Need assessment of men's u-21 football physical test - Dewi Nurhidayah; Yuliance Adii; Tri Setyo Guntoro; Sutoro Sutoro (Journal Of Sport Education (JOPE), 2023)
(English)One of the achievements in sports is determined by physical condition. Good physical condition will affect the player's game technique. Good physical condition is also obtained through programmed exercise. Training programming is of course determined using data on the athlete's initial physical condition. Therefore, it is necessary to measure the physical condition. The purpose of this study was to determine the physical test needs for men's U-21 football. This research is quantitative descriptive research with survey techniques using gform. The subjects in this study were trainers who were spread throughout Indonesia totaling 30 subjects. The instrument used in this study was a questionnaire distributed via the Google form. Data analysis techniques using descriptive statistics using the percentage formula. The results showed that 93% of the coaches stated that there had been no physical condition tests on male U-21 soccer players. 100% of coaches need specific instruments according to the sport and age, namely the men's U-21 football physical test. With that in mind, it is necessary to prepare the physical test for men's U-21 football. (Indonesian)Prestasi dalam olahraga salah satunya ditentukan oleh kondisi fisik. Kondisi fisik yang baik akan mempengaruhi teknik permainan pemain. Kondisi fisik yang baik juga diperoleh melalui latihan yang terprogram. Pemrograman latihan tentunya ditentukan dengan menggunakan data kondisi fisik awal atlet. Oleh karena itu, pengukuran kondisi fisik perlu dilakukan. Tujuan penelitian ini yaitu untuk mengetahui kebutuhan tes fisik sepak bola putra U-21. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan teknik survei menggunakan google form. Subyek dalam penelitian ini yaitu pelatih yang tersebar di seluruh Indonesia berjumlah 30 subjek. Instrumen yang digunakan dalam penelitian ini yaitu kuesioner yang disebar melalui google form. Teknik analisis data menggunakan statistik deskriptif menggunakan rumus persentase. Hasil penelitian menunjukkan 93% pelatih menyatakan belum ada tes fisik pada pemain sepak bola U-21 putra. 100% pelatih membutuhkan instrumen yang spesifik sesuai dengan cabang olahraga dan usia yaitu tes fisik sepak bola U-21 putra. Dengan begitu penyusunan tes fisik sepak bola U-21 putra perlu dilakukan.Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.